Systemic Phaeohyphomycosis in a Dog Caused by Cladophialophora bantiana - Alves, Rodrigo Cruz; Soares, Yanca Góes dos Santos; da Silveira, Gian Libânio; Silva, Francisco Cézar da; Carvalho, Fabrício Kleber de Lucena; de Souza, Almir Pereira; Galiza, Glauco José Nogueira de; Dantas, Antônio Flávio Medeiros (Acta Scientiae Veterinariae, 2022)
Background: Cladophialophora bantiana is a dematiaceous fungus that causes phaeohyphomycosis, a generic term used to describe a variety of unusual mycoses caused by fungi that have melanin in their cell wall. C. bantiana targets the central nervous system, commonly causing localized brain infections that may result in disseminated infections. In Brazil, minimal phaeohyphomycosis data are available, and information about C. bantiana infections in animals, especially canines, is scarce. Thus, the aim of this study was to describe the clinical and pathological aspects of systemic phaeohyphomycosis caused by C. bantiana in a dog. Case: A 1-year-old female Pit Bull presented with weight loss, reduced appetite, and a history of cutaneous lesions on the right thoracic limb; however, clinical evolution was not reported. The dog had reportedly given birth recently. Physical examination revealed thinness, pale ocular and oral mucosa, submandibular lymph nodes, and enlarged popliteal lymph nodes. The animal died after convulsive crises during hospitalization. At necropsy, white-yellowish multifocal nodules were observed in the liver and right kidney. The brain featured left cerebral hemisphere asymmetry with blood vessel congestion in the leptomeninges and an irregular brownish focal area on the surface of the right occipital cortex. Cross-sections of the formalin-fixed brain exhibited compression of the left lateral ventricle and the presence of grayish and friable multifocal areas in the gray matter of the left parietal and right occipital cortices. Fragments of the lesions were collected for histopathological and microbiological examination. Histologically, the lesions were similar, characterized by hepatitis, nephritis, and granulomatous and necrotizing meningoencephalitis, multifocal to coalescing, accentuated, chronic, and associated with numerous pigmented fungi. Fontana-Masson–stained fungi exhibited a strong black color. In cleared and unstained histological slides, brownish pigmentation was observed in the cytoplasm and walls of the fungi. C. bantiana was identified via microbiological cultivation. Discussion: A diagnosis of phaeohyphomycosis caused by C. bantiana was made based on the characteristic morphology of the microscopic lesions and confirmed via isolation in microbiological culture. As numerous species cause phaeohyphomycosis, specific confirmation of the etiologic agent using several diagnostic techniques is necessary. In histopathological examinations, pigmented fungal organisms are easily seen among lesions. However, in some cases, the pigment is not apparent in the tissues. FM staining is necessary to demonstrate the presence of the melanin in fungi. As in most phaeohyphomycosis cases, it was not possible to determine the primary portal of entry. However, the lesion on the right thoracic limb probably favored the penetration of the agent. In addition to cerebral lesions, severe lesions in the hepatic and renal parenchyma were observed, which are characteristic of systemic mycosis. Infection and clinical diseases are usually associated with immunocompromised; here, the gestation period may have had an immunosuppressive effect, favoring the proliferation and dissemination of the agent. It was concluded that phaeohyphomycosis caused by C. bantiana produced severe systemic lesions in the brain and organs of the abdominal cavity. Although uncommon, phaeohyphomycosis caused by Cladophialophora bantiana should be included as a differential diagnosis for other canine diseases that present with similar clinical symptoms. Keywords: canine, fungal diseases, dematiaceous fungi, Cladosporium trichoides, Xylohypha bantiana, melanin, Fontana-Masson